Metastatic pheochromocytoma complicated with Langerhans cell histiocytosis: a case report - Dai, Dandan; Xie, Jing (Frontiers in Endocrinology, 2025)
Pheochromocytoma is a neuroendocrine neoplasm that originates from chromaffin cells of the adrenal medulla. Langerhans cell histiocytosis (LCH) is a proliferative disease of histiocyte-like cells, often associated with activating mutations of the mitogen-activated protein kinase (MAPK) pathway. We present a case of a 49-year-old male with a history of pheochromocytoma, which metastasized to the inferior vena cava eight years after left adrenalectomy. At the same time, it was found that the pheochromocytoma in the metastasis was complicated with LCH, a combination that has not been previously reported. Genetic analysis was carried out by next-generation sequencing (NGS) technology. Somatic mutations of BRAF and RAD54B were detected in Langerhans cells and EPAS1 in pheochromocytoma.